Synthesis of Video Gain Equalizer via Distributed circuits - Vanvisa Chutchavong; Virote Pirajnanchai; Pongpan Rattanathanawan; Sudasawan Ngammongkolwong; Vorawut Puntapa; K. Janchitrapongvej (My University, 2025)
This paper presents a linear luminance and chrominance gain equalizer in video waveform transmission. Practically, the distributed devices have physical characteristics similar to the transmission line. Therefore, it can be employed to function in approximately as a passive lumped element. For this purpose, a novel transformation can be realized on equalizer using commemorated passive and active filters with uniformly distributed URC lines. In this paper we introduce two types of gain equalizers. The first type consists of resistive, conductive and capacitive, known as uniform GCR elements. The second type approximated by the uniformly distributed RC transfer function. As the results the proposed gain equalizer prove in equalizing both the luminance and chrominance gain distortions correction. From the simulation results, it is shown that the proposed distributed circuit gives good amplitude chrominance characteristic for both types of luminance gain equalizers.
Keywords: Neural Networks and Applications; Blind Source Separation Techniques; Advanced Data Compression Techniques